Integration of Multicultural Counseling Theories, Community Assets and Intercultural Communication in Empowering Coastal Children - Jarnawi; Fairus; Sulaeman, Arif Ramdan; Fakhri; Nursaady Ibrahim (Universitas PGRI Yogyakarta, 2026)
Empowering coastal children is a complex developmental challenge requiring strategies that address psychological, social, and cultural dimensions within maritime communities. This systematic literature review examined how multicultural counseling, community asset development, and intercultural communication can enhance empowerment strategies. A systematic screening of academic databases over ten years yielded ten relevant studies from an initial 306 articles using strict inclusion criteria. Analysis identified convergence across three key dimensions: culturally sensitive pedagogical approaches, mobilization of community assets through linking resources and raising awareness of local capabilities, and universal communication patterns that transcend cultural boundaries. The integrative model highlighted the effectiveness of peer-led programs and experiential learning in promoting empowerment. Findings indicate that combining multicultural counseling principles, strategic community resource use, and intercultural communication creates a robust framework for coastal children’s development. This approach ensures cultural responsiveness while maintaining universal developmental principles, providing practical, evidence-based guidance for holistic empowerment interventions in diverse maritime settings. Keywords: coastal child empowerment, multicultural counseling, community assets